The Training for Skill Assessment Designing Based on Characters on Teachers of Junior High School - Kurnia Ningsih; Ahmad Yani (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2018)
The revised 2013 curriculum requires skill assessment by involving students' characters. In giving an assessment, a teacher performs one unit that cannot be separated from one another between the assessment of skills and the assessment of character in students. With the demands in assessing the 2013 revised Curriculum, the purpose of community service activities is to assist teachers in making character-based skills assessments. The method used in this activity is training and mentoring, with partner schools is Pontianak 11 State Junior High School. There were 32 participants in the training and mentoring activities, while 20 people filled out the response questionnaire. The results of the training showed that the participants involved were very enthusiastic, and followed the activities to completion. Based on the questionnaire given, overall it was found that the mastery of the teacher on character-based skills assessment was 85.75% with good categories. In detail, the character aspects of the 2013 curriculum are 91.75%, and the skills assessment is 79.75% the teacher states that they master well.